2021
DOI: 10.1111/nmo.14257
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal‐enriched extracellular vesicles in individuals with IBS: A pilot study of COMT and BDNF

Abstract: Background: Irritable bowel syndrome (IBS) is characterized by abdominal pain, bowel habit alterations, and psychiatric comorbidities. Although pathophysiology remains incompletely understood, prior work demonstrates associations with brain-derived neurotrophic factor (BDNF) and catechol-O-methyltransferase (COMT). The purpose of this study was to quantify BDNF and COMT in plasma and in neuronal-enriched extracellular vesicles (nEVs), assess relationships with psychological symptoms, and gain insight on the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Proposed mechanisms on how exercise may increase BDNF levels in neurons include: (i) effects through the PGC1α-dependent myokine, irisin [ 33 ], (ii) the myokine Cathepsin B, which when increased peripherally by exercise can cross the BBB and enhance BDNF production and hence neurogenesis [ 39 ] and (iii) β-hydroxybutyrate, which also increases during aerobic exercise and increases BDNF expression in the brain [ 37 ]. As previously shown, both proBDNF and BDNF are present in NDEVs, at higher levels compared to plasma [ 40 ]. Moreover, NDEV proBDNF, but not BDNF, was associated with physical activity in a large longitudinal cohort of aging [ 41 ].…”
Section: Discussionmentioning
confidence: 93%
“…Proposed mechanisms on how exercise may increase BDNF levels in neurons include: (i) effects through the PGC1α-dependent myokine, irisin [ 33 ], (ii) the myokine Cathepsin B, which when increased peripherally by exercise can cross the BBB and enhance BDNF production and hence neurogenesis [ 39 ] and (iii) β-hydroxybutyrate, which also increases during aerobic exercise and increases BDNF expression in the brain [ 37 ]. As previously shown, both proBDNF and BDNF are present in NDEVs, at higher levels compared to plasma [ 40 ]. Moreover, NDEV proBDNF, but not BDNF, was associated with physical activity in a large longitudinal cohort of aging [ 41 ].…”
Section: Discussionmentioning
confidence: 93%
“…menstrual pain [74], anxiety [75,76], and depression [77,78]. In the context of IBS, our previous research revealed decreased plasma BDNF levels in IBS patients compared to non-IBS individuals [79]. Other studies have also found an association between lower serum BDNF levels and higher levels of anxiety and depressive symptoms in individuals with IBS [80].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have extensively explored the genetic impact of rs6265, encompassing not only pain but also psychological and other somatic pain traits that are highly prevalent in individuals with IBS, including migraines [72], fibromyalgic pain [73], menstrual pain [74], anxiety [75, 76], and depression [77, 78]. In the context of IBS, our previous research revealed decreased plasma BDNF levels in IBS patients compared to non-IBS individuals [79]. Other studies have also found an association between lower serum BDNF levels and higher levels of anxiety and depressive symptoms in individuals with IBS [80].…”
Section: Discussionmentioning
confidence: 99%
“…Proposed mechanisms on how exercise may increase BDNF levels in neurons include: (i) effects through the PGC1α-dependent myokine, irisin (33), (ii) the myokine Cathepsin B, which when increased peripherally by exercise can cross the BBB and enhance BDNF production and hence neurogenesis (39) and (iii) β-hydroxybutyrate, which also increases during aerobic exercise and increases BDNF expression in the brain (37). As previously shown, both proBDNF and BDNF are present in NDEVs, at higher levels compared to plasma (40). Moreover, NDEV proBDNF, but not BDNF, was associated with physical activity in a large longitudinal cohort of aging (41).…”
Section: Discussionmentioning
confidence: 98%